Knowledge of Good Blood Culture Sampling Practice among Healthcare Staffs in An Emergency Department - Are We Getting It Right? - Chew, K S; Mohd Hashairi, F; Jusoh, A F; Aziz, A A; Nik Hisamuddin, N A R; Siti Asma, H (2013)
BACKGROUND